Efeito do rainfastness e adjuvante na aplicação de fungicidas foliares em cultivares de soja - Debortoli, Monica Paula (2008)
Deposition, distribution and tenacity on the leaf surface can influence the efficacy of the fungicide. The effect of rainfall after the spray might run out fungicides of contact from leaf surface. It can also remove the systemic fungicides, if the spray occurs right after the fungicide application. The goals of this work were (i) performance of fungicides due to the drop spectrum under simulated conditions of rainfall on soybean rust control and (ii) determine the interference of rainfall on the biological efficacy of fungicides in different of soybean cultivars to control Phakopsora pachyrhizi. Two experiments were run out in greenhouse conditions. Experiment 1 studied three spray nozzles (twin flat spray - TJ60 11002; extended range flat spray - XR 11002 and wide angle flat spray - TT 11002), spray a fungicide with and without adjuvant, and four intervals of rain after spraying (0, 30, 60 and 120 minutes); two control treatments (without chemical spray and without rain). Experiment 2 rated the performance of four fungicides (Azoxystrobin + Cyproconazol; Pyraclostrobin + Epoxyconazol, Pycoxistrobin + Cyproconazol and Tebuconazol 250 EC) sprayed on seven cultivars (Coodetec 214 RR, Coodetec 219 RR, Monsoy 8000 RR, Monsoy 8080 RR, Fundacep 56 RR, FMT Tabarana and Nidera 7636 RR). Treatments were exposed to simulated rain at intervals of 0, 30, 60, 120 and 240 minutes after spray. The fungicides were sprayed with CO2 pressurized sprayer. The simulated rain produced a precipitation intensity of 20 mm/4min. The simulated rain caused negative effect on the performance of spraying nozzles and the effectiveness of Phakopsora pachyrhizi and powdery mildew control. Fungicide application with no addition of adjuvant affected the efficacy of soybean rust control due to the occurrence of rain immediately after the spraying. The drops produced by the nozzles XR showed the best drop deposition to the control of the soybean rust. In the absence of adjuvant it was observed less negative effect caused by the rain. When the adjuvant was added to the fungicide, it provided less control than the nozzle TT at 0 and 30 minutes after spraying. It was observed relationship between influences of the rainfastness on the efficiency of disease control provided by fungicides in different levels for the seven cultivars tested. The cultivars Msoy 8000 and Nidera 7636 were more showed higher product washing soon after spraying showing AUCPD superior to the other cultivars when sprayed azoxystrobin + cyproconazol. However the cultivars CD 214, CD 219 and FMT Tabarana suffered minor effect due to the rainfastness. It showed significant differences from the other cultivars as much to the final severity of rust as the AUCPD for the same fungicide. Occurrence of rain immediately after the spraying of pyraclostrobin + epoxyconazol was observed superiority in the disease control of the cultivars Cep 56, Nidera 7636 and CD 219 with smaller values of severity and final AUCPD. The efficiency of control of the fungicide pycoxistrobin + cyproconazol was less affected in cultivars Cep 56 and Nidera 7636 by rainfastness. The fungicide tebuconazol was little affected by rainfastness when sprayed in cultivars Cep 56 and CD 219, but in the CD 214 and Nidera 7636 was negative effect of rain. Yield per plant and weight of a thousand grains showed similar trend considering the final severity and AUCPD of the soybean rust.